2008
DOI: 10.1007/s11738-008-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthesis of pea plants under different iron supply

Abstract: Soil conditions, leading to iron deficiency or toxicity, are widespread in nature. Our objective was to study the effect of Fe supply, ranging from complete deficiency to excess, on growth and on some photosynthetic indices of pea plants. Both iron deficiency and toxicity decreased shoot and root growth. Complete deficiency resulted in a lower shoot/root ratio and a higher content of dry biomass per unit of fresh biomass in roots, while iron excess led to higher content of dry biomass per unit of fresh biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 24 publications
5
22
0
1
Order By: Relevance
“…However, adverse environmental conditions and an excess or deficiency of Fe can affect this process. One of the characteristic symptoms of iron deficiency are: (a) leaf chlorosis due to the decrease of chlorophyll and carotenoid biosynthesis (Abadía et al, 1999); (b) a reduced net CO 2 assimilation rate (Sharma, 2007); (c) a disorganisation of photosynthetic complexes (Timperio et al, 2007); and (d) an increase in the stomatal resistance coupled with a decline of the transpiration rate (Nenova, 2009). In contrast, excess iron can lead to the appearance of brown spots on the leaves, which often leads to necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse environmental conditions and an excess or deficiency of Fe can affect this process. One of the characteristic symptoms of iron deficiency are: (a) leaf chlorosis due to the decrease of chlorophyll and carotenoid biosynthesis (Abadía et al, 1999); (b) a reduced net CO 2 assimilation rate (Sharma, 2007); (c) a disorganisation of photosynthetic complexes (Timperio et al, 2007); and (d) an increase in the stomatal resistance coupled with a decline of the transpiration rate (Nenova, 2009). In contrast, excess iron can lead to the appearance of brown spots on the leaves, which often leads to necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in this study the rate of photosynthesis is higher in the control plants compared to other applications. Chouliaras et al (2004a) claimed that iron deficiency resulted in a significant decrease of Pn in citrus plants, and several authors indicated that the lime-induced iron deficiency reduced the net photosynthetic rate in the leaves (Morales et al, 1994;Abadía et al, 1999;Larbi et al, 2006;Nenova, 2009). Iron deficiency diminished the activity of the stroma enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of mineral elements also influences the content of photosynthetic dyes, especially those that are components of chlorophyll, proteins and that are involved in electron transfer in the light reaction phase, nitrogen, magnesium, iron, sulphur, manganese, phosphorus and potassium (Balakrishnan et al 2000;Candan & Tarhan 2003;Pinkard et al 2006;Nenova 2009;Zhou et al 2011). The deficiency of nitrogen, magnesium and iron hinders the synthesis of chlorophyll, while the deficiency of magnesium causes a decrease in the content of chlorophyll, especially in older leaves (Abadía et al 1996;Kozłowska & Politycka 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution in the city has been considered as one of the most serious environmental problems (Juda-Rezler 2000;Buchan 2005). Acidic deposition and heavy metal accumulation may be contributing to plant population and plant communities declines and may cause adverse responses manifested in their growth, physiology, ecological structure and floristic composition (Drzewiecka-Matuszek et al 2005;Nenova 2009;Zhou et al 2011). Determination of photosynthetic pigments has been a major research subject in the study on air pollution effects on vegetation (Bell & Treshow 2002;Merkisz et al 2005).…”
Section: Introductionmentioning
confidence: 99%